2020
DOI: 10.1186/s12885-020-07270-w
|View full text |Cite
|
Sign up to set email alerts
|

WeChat app-based reinforced education improves the quality of opioid titration treatment of cancer-related pain in outpatients: a randomized control study

Abstract: Background: As inadequate pain communication contributes to difficulties in optimizing outcomes of outpatients, we investigated the effect of reinforced education using WeChat App to the opioid titration treatment of cancerrelated pain in the outpatient setting. Methods: We conducted a prospective study to compare reinforced education using Wechat with care as usual from February to December 2019. Patients in the reinforced education group received reinforced education via Wechat, while those in the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…A total of 80% (24/30) of the studies [16,19,[25][26][27][28][29][30][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49] involving 4822 participants used various scales to report the outcome of QOL. Of these 24 studies, 8 (33%) [19,26,27,37,39,40,42,43] focused on patients with breast cancer, and the other 16 (67%) included patients with multiple types of cancer (such as breast cancer, brain cancer, and prostate cancer).…”
Section: Effects On Qolmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 80% (24/30) of the studies [16,19,[25][26][27][28][29][30][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49] involving 4822 participants used various scales to report the outcome of QOL. Of these 24 studies, 8 (33%) [19,26,27,37,39,40,42,43] focused on patients with breast cancer, and the other 16 (67%) included patients with multiple types of cancer (such as breast cancer, brain cancer, and prostate cancer).…”
Section: Effects On Qolmentioning
confidence: 99%
“…Owing to the significant heterogeneity among the studies (P<.001; I 2 =77%), the results were pooled using a random-effects model. Overall, the mHealth app interventions significantly improved cancer-related QOL scores (SMD=0.39, 95% CI 0.27-0.51; P<.001; Figure 3 [16,19,[25][26][27][28][29][30][33][34][35][37][38][39][40][41][42][43][44][45][46][47][48][49]). We conducted subgroup analyses according to intervention duration, type of cancer, intervention theory, treatment strategy, and intervention delivery format to investigate potential sources of heterogeneity.…”
Section: Effects On Qolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is free of charge, works in real time, and is easy to operate. The study by Zhang et al has confirmed that WeChat is a good tool to improve the health knowledge level of patients and that it is beneficial for enhancing the perioperative nursing management of the nursing personnel [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WeChat platform is widely used in various fields. The medical applications of the platform have mainly involved health management issues such as disease feedback, diet intervention, and behavior education, and many researchers have used the WeChat platform to manage the health of patients to achieve positive results (6)(7)(8). However, a probiotic supplement project based on WeChat platform for patients with mild to moderate UC has not been reported nationally and internationally to date.…”
Section: Introductionmentioning
confidence: 99%